Aspect-based adaptation for ubiquitous software - Zambrano Polo y La Borda, Arturo Federico
Information should be available everytime everywhere in the ubiquitous computing world. Environment conditions such as bandwidth, server availability, physical resources, etc. are volatile require sophisticated adaptive capabilities. Designing this kind of systems is a complex task, since a lot of concerns could get mixed with the application’s core functionality. Aspect-Oriented Programming (AOP) [1] arises as a promising tool in order to design develop ubiquitous applications, because of its ability to separate cross-cutting concerns. In this paper we propose an AOP-based architecture to decouple the several concerns that ubiquitous software comprises.